Analysis of Financial Performance Using Budget Absorption Indicators - Safriansah Safriansah; Nizwan Zukhri; Andriyansah Andriyansah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Budget absorption is one indicator in measuring the performance of the state revenue and expenditure budget. Most of the budget realization occurred in the fourth quarter. The absorption of the budget, especially expenditure on goods and services, has a significant effect in driving economic growth. The research objective was to analyze the effect of budget planning, budget execution, government internal control systems on budget absorption, financial performance at the "Forest Area Consolidation Hall in Sumatra Region with budget absorption as a mediating relationship. This research uses descriptive quantitative method. The number of samples in this study were 215 respondents. The sampling technique in this research is saturated sampling. The research results show that there is an effect of budget planning, budget execution and government internal control systems on budget absorption at the Forest Area Consolidation Center in Sumatra Region. In addition, budget absorption also affects financial performance at the Forest Area Consolidation Center in Sumatra Region. Budget Absorption Mediates the Relationship between Budget Planning and Financial Performance at the Forest Area Consolidation Center in Sumatra Region. Absorption of Budget Mediates the Relationship between Budget Implementation and Financial Performance at the Forest Area Consolidation Center in Sumatra Region. Absorption of Budget Mediates the Relationship between the Government's Internal Control System and Financial Performance at the Forest Area Consolidation Center in Sumatra Region.